Bioinspired diamond composites and their dynamic shock performance. (January 2022) - Li, Yuanyuan; He, Hongliang; Wang, Qiming; Zhang, Lu; Yu, Yin; He, Duanwei
Abstract: The design of high-strength and high-toughness materials that can sustain high shock-wave loadings is crucial for both armor and civil applications. We propose a bioinspired diamond composite that mimics the brick-and-mortar arrangement of nacre from mollusk shells and evaluate its performance for different diamond brick contents using lattice-spring model. In this work, we present a systematic investigation elucidating the effects of volume fraction of diamond brick, on the shock compression response of bioinspired diamond composites. By comparing the nacre-like diamond composite with traditional diamond composite, it was found that the nacre-like diamond composite can reduce damage degree in diamond composite, and improve dynamic strength of diamond composite. More importantly, the damage evolution analysis of the impacted nacre-like diamond composite indicated that there is large-scale crack deflection, which is only cause slight damage to the diamond brick. The obtained numerical results may provide valuable insights into the preparation of superhard composites for numerous engineering applications. Highlights: Superhard diamond composites with a nacre-like architecture were designed. Macroscopic shock-wave propagation and mesoscopic damage evolution were analyzed. The nacre-like diamond composites exhibited reduced localized damage under shock compression. The nacre-like diamond composites displayed improved dynamic strength.